2004
DOI: 10.1097/00002030-200405210-00012
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of Fc receptor IIa for IgG in infants is associated with susceptibility to perinatal HIV-1 infection

Abstract: This study provides the first evidence that the infant Fc gamma RIIa His/His131 genotype is associated with susceptibility to perinatal HIV-1 transmission and further suggests that there is a dose-response relationship for the effect of the Fc gamma RIIa His131 gene on transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 28 publications
5
54
1
Order By: Relevance
“…Highaffinity polymorphisms of Fc␥R3a, while protective in monoclonal antibody therapy of cancer, have been associated with HIV progression (43). Similarly, the allele of Fc␥R2a with improved recognition of IgG2 subclass antibodies has been found to be a risk factor in neonatal HIV transmission (22), whereas it has been associated with protection from progression in adults (21). Yet passive-transfer studies of both neutralizing monoclonal and vaccine-induced nonneutralizing antibodies have implicated antibody effector functions in protection (9,44,45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Highaffinity polymorphisms of Fc␥R3a, while protective in monoclonal antibody therapy of cancer, have been associated with HIV progression (43). Similarly, the allele of Fc␥R2a with improved recognition of IgG2 subclass antibodies has been found to be a risk factor in neonatal HIV transmission (22), whereas it has been associated with protection from progression in adults (21). Yet passive-transfer studies of both neutralizing monoclonal and vaccine-induced nonneutralizing antibodies have implicated antibody effector functions in protection (9,44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence support the importance of phagocytosis in HIV infection. First, Fc␥R2a polymorphisms have been found to correlate with disease progression (21) and susceptibility (22). Second, IgG2 subclass antibodies, in combination with the Fc␥R2a allele capable of interacting with IgG2, are associated with delayed progression (23).…”
mentioning
confidence: 99%
“…Otherwise, we might expect the high-affinity genotypes (VVs and HHs) to be associated with a lower risk of infection at any given level of serum ADCVI activity because the higher affinity genotypes mediate better ADCC activity (40,41). In contrast, high-affinity genotypes may enhance the risk of infection through an Ab-dependent mechanism, as suggested by the finding that infants homozygous for Fc␥RIIa H have at least a 2.2-fold increased risk of perinatal HIV infection compared with infants having one or no H allele (42). We propose that our results reflect opposing Ab functions: ADCVI on the one hand and virus enhancement or blocking of beneficial functions in contrast.…”
Section: Discussionmentioning
confidence: 99%
“…The high affinity HH genotype may be disadvantageous where immune-complexed pathogens establish infection within phagocytes or where IgG2 Abs block beneficial Fc␥R-triggered events. With respect to HIV, Brouwer et al reported a 2-fold increased risk of perinatal infection in HH infants compared with RR infants (35). They suggested that maternal Ab bound to virus may have facilitated infection of macrophages or dendritic cells bearing the higher affinity HH receptor.…”
Section: Discussionmentioning
confidence: 99%